Identification and Genotyping of Pathogenic Leptospira Circulating among Rodents in the City of St. Petersburg - R. R. Baimova; E. G. Riabiko; D. I. Grechishkina; I. A. Karmokov; E. S. Khalilov; I. S. Lyzenko; G. A. Lunina; Yu. V. Ostankova; N. K. Tokarevich; I. R. Zheltakova; I. A. Chmyr (Проблемы особо опасных инфекций, 2025)
The aim of the work was to determine the rate of infection by various Leptospira genomospecies of wild and synanthropic small mammals collected on the territory of St. Petersburg. Materials and methods. The capture of wild and synanthropic small mammals was carried out using Gero-type traps in the Kurortny and Kirovsky districts of St. Petersburg between September and October, 2021. The study of samples for the presence of Leptospira spp. DNA was performed applying PCR with primers selected for the lipL32 gene fragment. Genotyping of samples was conducted using primers for fragments of the secY and rpoB genes. Results and discussion. DNA of pathogenic Leptospira was detected in 8 samples, which amounted to (4.2±1.5) % of the total number of samples (190). The infection rate of gray rats collected in the Kirovsky district was (11.1±5.2) % (4/36). The infection rate of wild rodents collected in the Kurortny district was (3.7±2.6) % (2/54) for yellow-throated mice, and (2.0±1.4) % for bank voles (2/100). Based on the results of analysis of sequences obtained, the circulation of two pathogenic Leptospira species, L. interrogans and L. borgpetersenii, has been established. Our results confirm the circulation of Leptospira both among wild and synanthropic small mammals. The phylogenetic species of pathogenic Leptospira identified in our study are typical and associated with the studied rodents. In order to prevent the disease in humans, it is necessary to continue research aimed at identifying the circulation of pathogens in populations of wild and synanthropic small mammals. Deratization and activities aimed at educating residents of St. Petersburg about protection and prevention measures are required.